ORGANIZATION OF MEDICAL CARE TO CHILDREN WITH INFECTIOUS DISEASES IN THE CONDITIONS OF THREE-LEVEL SYSTEM - V. F. Serkov; А. S. Simakhodsky; О. V. Parkov; N. V. Andriyanycheva (Вопросы современной педиатрии, 2014)
The necessity for system structuring is defined by entry into force of the new normative documents directed on improvement of availability and quality of medical care, introduction of orders and standards of medical care delivery, providing staging and recommended volume. The three-level system operating in Saint-Petersburg is defined by normative documents of regional level and provides staging of medical care delivery to children with infectious diseases — one of the most frequent children pathologies. The main objective of the present article was to analyse the activity of three-level structure of the establishments rendering medical care to children with infectious diseases, to define the main objectives carried out at each level. The analysis of the main indicators shows the necessity for improvement of the system through rationalization depending on quality and volume of rendered medical care.